(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The divergence in the application of nomological network of concepts, constructs or variables in the report of conceptual frameworks at different levels of research is a concern to intellectual, skilled, and experienced research scholars. Sometimes, conceptual framework is erroneously reported as a collection of operational definition of concepts or even as a research design. This study is, therefore, in two folds: to x-ray the practical examples of more realistic and statistically testable conceptual models to foster less experienced researchers’ knowledge in developing and reporting conceptual framework in research; and to investigate students’ abilities in reporting conceptual framework in their research. The study adopted literature review approach with a mixed method design. This study sampled postgraduate (PG) students (N = 21), drawn from a faculty in Nnamdi Azikiwe University from 2019 to 2021, as well as PG students’ certified and approved theses/dissertations (N = 125). Observation checklist was used for the quantitative data collection, while a semi-structured interview was used for the qualitative data collection. Percentage was employed to analyze the quantitative data, while thematic analysis was applied for the qualitative data. Reviews demonstrated practical guides and examples of conceptual models. Findings revealed poor students’ skills in designing and reporting acceptable conceptual frameworks. Hence, recommendations were made for improvement.